THE INFLUENCE OF MARKETING MIX ON THE PURCHASE DECISION OF MOBILE JAMU SELLERS IN MERANTI DISTRICT, ASAHAN REGENCY (Case Study: Mrs. Mamy's Herbal Medicine Business) - Devi Syahfitri; Suryadi Suryadi; Riani Riani (LPPM Universitas Malikussaleh - Indonesia, 2025)
This research was conducted in Meranti District, Asahan Regency, focusing on the mobile herbal medicine business of Mrs. Mamy in June 2024. To meet consumer needs, Mrs. Mamy's mobile herbal medicine business must consider the four marketing mix elements: product, price, promotion, and place. These elements interrelate and impact consumer purchasing decisions for Mrs. Mamy's mobile herbal medicine. The method used was Multiple Linear Regression with SPSS 29. The resulting multiple linear regression equation from the study is Y = 20.511 + 0.003X‚ - 0.314X‚‚ + 0.300X‚ƒ - 0.129X‚„. The F-test results show that the variables product, price, promotion, and place significantly affect consumer purchasing decisions with an F-value of 3.290 and a significance level of 0.019 < 0.05. The t-test results indicate that the price and promotion variables positively and significantly influence consumer purchasing decisions with a significance level of 0.021 < 0.05. In contrast, the product and place variables do not significantly influence consumer purchasing decisions, as their significance values are greater than the alpha level of 0.05.).